Répondre :
Bonsoir,
A=x²+2xy+2
pour x=-3 et y=-2
9 + (2*-3*-2) +2=
9 + 12 +2 = 23
B=(x+y)(x-y)
pour x =-4 et y =-1
(-4-1) ( -4+1) =
-5 * -3 = 15
C=4x + 3y
pour x=-3 et y =-2
4*-3 + 3* -2=
-12 -6= -18
Bonsoir
A=x2+2xy+2 pour x=-3 et y=-2
A = (- 3)² + 2 * (- 3) * (- 2) + 2
A = 9 - 6 * (- 2) + 2
A = 9 + 12 + 2
A = 23
B=(x+y)(x-y) pour x =-4 et y =-1
B = (- 4 - 1) (- 4 - (- 1))
B = (- 5) * (- 4 + 1)
B = (- 5) * (- 3)
B = 15
C=4x + 3y pour x=-3 et y =-2
C = 4 * (- 3) + 3 * (- 2)
C = - 12 - 6
C = - 18.